2024
DOI: 10.3233/ies-230077
|View full text |Cite
|
Sign up to set email alerts
|

Continuous palm cooling’s effect on heat transfer and physiology

N.L. Patel,
P.M. Quesada,
J. Wellwood
et al.

Abstract: BACKGROUND: Excess heat accrual is perhaps the body’s most dangerous exercise-induced stressor. While palm cooling uses conduction to reduce body temperatures, to date the volume of heat transferred by this treatment resulting from exercise is unknown. OBJECTIVE: Asses continuous palm cooling’s impact on heat transfer and physiology. METHODS: Thirty-one subjects did two workouts; one with, and one without, palm cooling. Workouts entailed consecutive stages of submaximal pedaling against prescribed workloads. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Palm cooling led to significant ergogenic and physiological benefits when compared with a noncooling condition (24)(25)(26)(27). Many benefits were attributed to body heat removal; a recent study showed palm cooling elicited 32% higher heat transfer rates during submaximal exercise, as compared with non-palm cooling workouts (24,31). To best facilitate palm cooling, gloves were fabricated to combat body heat accrual (27,31).…”
Section: Exertional Heat Illness Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Palm cooling led to significant ergogenic and physiological benefits when compared with a noncooling condition (24)(25)(26)(27). Many benefits were attributed to body heat removal; a recent study showed palm cooling elicited 32% higher heat transfer rates during submaximal exercise, as compared with non-palm cooling workouts (24,31). To best facilitate palm cooling, gloves were fabricated to combat body heat accrual (27,31).…”
Section: Exertional Heat Illness Preventionmentioning
confidence: 99%
“…Many benefits were attributed to body heat removal; a recent study showed palm cooling elicited 32% higher heat transfer rates during submaximal exercise, as compared with non-palm cooling workouts (24,31). To best facilitate palm cooling, gloves were fabricated to combat body heat accrual (27,31). The gloves, developed from those marketed to the general public, appear in various configurations (see Figure ).…”
Section: Exertional Heat Illness Preventionmentioning
confidence: 99%
See 1 more Smart Citation